Porous titanium/hydroxyapatite interpenetrating phase composites with optimal mechanical and biological properties for personalized bone repair - Oliver-Urrutia, Carolina; Kashimbetova, Adelia; Slámečka, Karel; Casas-Luna, Mariano; Matula, Jan; Sumbalova Koledova, Zuzana; Kaiser, Jozef; Čelko, Ladislav; Montufar, Edgar B (Biomaterials advances, 2025)
This study introduces the first fabrication of porous titanium/hydroxyapatite interpenetrating phase composites through an innovative processing method. The approach combines additive manufacturing of a customized titanium skeleton with the infiltration of an injectable hydroxyapatite foam, followed by in situ foam hardening at physiological temperature. This biomimetic process circumvents ceramic sintering and metal casting, effectively avoiding the formation of secondary phases that can impair mechanical performance. Hydroxyapatite foams, prepared using two foaming agents (polysorbate 80 and gelatine), significantly reinforce the titanium skeleton while preserving the microstructural characteristics essential for osteoinductive properties. The strengthening mechanisms rely on the conformation of the foams to the titanium surface, thereby enabling stable mechanical interlocking and effective interfacial stress transfer. This, combined with the mechanical constriction of phases, enhances damage tolerance and mechanical reliability of the interpenetrating phase composites. In addition, the interpenetrating phase composites feature a network of concave pores with an optimal size for bone repair, support human osteoblast proliferation, and exhibit mechanical properties compatible with bone, offering a promising solution for the efficient and personalized reconstruction of large bone defects. The results demonstrate a significant advancement in composite fabrication, integrating the benefits of additive manufacturing for bone repair with the osteogenic capacity of calcium phosphate ceramics.
Keywords: tkáňové podpůrné struktury; hydroxyapatit; biokompatibilní materiály; Osteoblasts; Bone repair; Self-hardening; Osteogenesis; Bone Substitutes; Bone and Bones; Humans; Titanium; proliferace buněk; osteogeneze; Durapatite; lidé; kosti a kostní tkáň; Biocompatible Materials; Tissue Scaffolds; titan; testování materiálů; regenerace kostí; Porosity; Cell Proliferation; Materials Testing; osteoblasty; poréznost; Infiltration; Hydroxyapatite; Ceramic matrix composite; kostní náhrady; Bone Regeneration